(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2015)
The essay questions on the development of the statement of the Court of Justice, according to which: «... Article 6 , paragraph 2, letter c) of Directive 98/44 , must be interpreted as meaning that an unfertilized human egg which through par-thenogenesis, has been induced to divide and grow is not a “human embryo” within the meaning of that provision if , in the light of current knowledge of science, it is free, as such , the inherent capacity to develop into a human being…». Consequent-ly, it reflects the possibility that, in future, the uses of such a body for industrial or commercial purposes are, in principle, subject to patent.